Accumulation of acetaldehyde in aldh2.1-/- zebrafish causes increased retinal angiogenesis and impaired glucose metabolism - Wohlfart, David Philipp; Lou, Bowen; Heim, Chiara; Morgenstern, Jakob; Fleming, Thomas; Sticht, Carsten; Haußer-Siller, Ingrid; Hell, Rüdiger; Hammes, Hans-Peter; Szendrödi, Julia; Nawroth, Peter Paul; Kroll, Jens (Redox Biology, 2022)
Reactive carbonyl species (RCS) are spontaneously formed in the metabolism and modify and impair the function of DNA, proteins and lipids leading to several organ complications. In zebrafish, knockout of the RCS detoxifying enzymes glyoxalase 1 (Glo 1), aldehyde dehydrogenase 3a1 (Aldh3a1) and aldo-ketoreductase 1a1a (Akr1a1a) showed a signature of elevated RCS which specifically regulated glucose metabolism, hyperglycemia and diabetic organ damage. aldh2.1 was compensatory upregulated in glo1−/− animals and therefore this study aimed to investigate the detoxification ability for RCS by Aldh2.1 in zebrafish independent of ethanol exposure. aldh2.1 knockout zebrafish were generated using CRISPR/Cas9 and subsequently analyzed on a histological, metabolomic and transcriptomic level. aldh2.1−/− zebrafish displayed increased endogenous acetaldehyde (AA) inducing an increased angiogenesis in retinal vasculature. Expression and pharmacological interventional studies identified an imbalance of c-Jun N-terminal kinase (JNK) and p38 MAPK induced by AA, which mediate an activation of angiogenesis. Moreover, increased AA in aldh2.1−/− zebrafish did not induce hyperglycemia, instead AA inhibited the expression of glucokinase (gck) and glucose-6-phosphatase (g6pc), which led to an impaired glucose metabolism. In conclusion, the data have identified AA as the preferred substrate for Aldh2.1's detoxification ability, which subsequently causes microvascular organ damage and impaired glucose metabolism.
Im Titel ist "-/-" hochgestellt
Gesehen am 01.06.2022